High Speed Electro-Absorption Modulator for Long Range Retroreflective Free Space Optics - Quintana, C.; Wang, Q.; Jakonis, D.; Piao, X.; Erry, G.; Platt, D.; Thueux, Y.; Gomez, A.; Faulkner, G.; Chun, H.; Salter, M.; O'Brien, D. (IEEE photonics technology letters, 2017)
In this letter, we present the design and implementation of a pixelated electro-absorption modulator-based modulating retroreflector (MRR) for high-speed optical wireless communications. The modulator is based on a multiple quantum well structure embedded in an asymmetric Fabry-Perot cavity. This MRR was used in an outdoor link, operating at 150 Mb/s with a bit error rate (BER) of 1.22 × 10 -6 at a range of 200 m. The system was also tested in laboratory-controlled conditions achieving a data rate of 200 Mb/s with a BER of 2 × 10 -4 . To the best of our knowledge, this is the fastest retroreflective free-space optics demonstration in both the indoor and outdoor environments.